Hubungan Riwayat ASI Eksklusif, Asupan Zink, dan Frekuensi Sakit dengan Kejadian Stunting pada Balita - Hafifah Rahmi Indita; Ade Lia Ramadani; Lailatul Muniroh (Universitas Airlangga, 2023)
Background: Stunting is defined as a problem in growth and development caused by undernutrition, repeated infectious disease, and insufficient stimulation. Despite decrease in Indonesia's stunting prevalence had occurred, stunting remained as a serious nutritional issue and needed to be resolved. Objectives: To determine the relationship between history of exclusive breastfeeding, zinc intake, and frequency of infectious disease with stunting incidence in toddlers Methods: The study design used a case-control study with simple random sampling. Samples were 22 toddlers in each group in Gunung Tugel and Karang Anyar Village, Bantaran, Probolinggo, East Java. Data was obtained by questionnaire regarding exclusive breastfeeding history, zinc adequacy level, and frequency of infection. Toddlers' nutritional status data were collected by direct measurement. Data collected were analyzed with chi-square test. Results: Exclusive breastfeeding history was found higher in control group (63,6%). Zinc deficiency was found higher in case group (81,8%). Less infection frequency was found higher in control group (95%). There was no relationship between exclusive breastfeeding history (p=0,226), zinc adequacy level (p=0,472) and stunting incidence in toddlers. There was a relationship between infectious disease frequency with stunting incidence in toddlers (p=0,004). Conclusions: Toddlers with higher infection frequency have a higher stunting risk.